2009
DOI: 10.1182/blood-2008-07-170589
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-29b induces global DNA hypomethylation and tumor suppressor gene reexpression in acute myeloid leukemia by targeting directly DNMT3A and 3B and indirectly DNMT1

Abstract: Aberrant DNA hypermethylation contributes to myeloid leukemogenesis by silencing structurally normal genes involved in hematopoiesis. MicroRNAs (miRNAs) are noncoding RNAs that regulate gene expression by targeting protein-coding mRNAs. Recently, miRNAs have been shown to play a role as both targets and effectors in gene hypermethylation and silencing in malignant cells. In the current study, we showed that enforced expression of miR-29b in acute myeloid leukemia cells resulted in marked reduction of the expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
582
7
18

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 719 publications
(643 citation statements)
references
References 27 publications
(47 reference statements)
31
582
7
18
Order By: Relevance
“…Thus miR148a could downregulate DNMT expression, which decreased the methylation of RUNX3, and RUNX3 protein levels increased. Our findings are consistent with several studies that provide evidence for miRNA-induced regulation of promoter methylation through DNMTs (Braconi et al, 2010;Garzon et al, 2009;Li et al, 2012;Pan et al, 2010;Wang et al, 2012;Zhao et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus miR148a could downregulate DNMT expression, which decreased the methylation of RUNX3, and RUNX3 protein levels increased. Our findings are consistent with several studies that provide evidence for miRNA-induced regulation of promoter methylation through DNMTs (Braconi et al, 2010;Garzon et al, 2009;Li et al, 2012;Pan et al, 2010;Wang et al, 2012;Zhao et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…We believe that in gastric cancer this miRNA-epigenetic feedback may further lead to the downregulation of methylation-sensitive genes, such as P16, RUNX3, and E-cadherin, through the hypermethylation of promoters. We must note that miR-152 , miR-126 (Zhao et al, 2011), and miR-29 (Garzon et al, 2009;Li et al, 2012) have also been observed to target DNMT1. Consequently, our further studies will focus on these miRNAs, which may cooperatively target DNMT1 and further regulate the expression of methylation-sensitive genes.…”
Section: Discussionmentioning
confidence: 97%
“…24,25 Recent studies showed that DNMTs may be a target of miR-29 family. 26,27 Based on these, the effects of loss of HOTAIR on the miR-29 family were examined. In vivo and in vitro, HOTAIR knockdown increased miR-29b level with no effect on miR-29a and miR-29c levels ( Figures 6A and 6B).…”
Section: Mir-29b Regulates Pten Expression By Targeting Dnmt3b and Ismentioning
confidence: 99%
“…18,[20][21][22][23][24][25][26][27][28] Here we examine the expression of genes listed in Supplementary Table 3 for their response to transfection of control miRNA, miR-125B antagomiR, miR-29B mimic and miR-125B antagomiR in combination with miR-29B mimic. Figure 6a shows that MYBL2, AKT2, CDK4 and SP1 are inhibited by miR-29B mimic in THP-1 cells; we also observe that AKT2 and CDK4 are further inhibited by the addition of miR-125B antagomiR.…”
Section: Mir-29b and Mir-125b Gene Targets In Human Amlmentioning
confidence: 99%